Check It!: A Randomized Pilot of a Positive Psychology Intervention to Improve Adherence in Adolescents With Type 1 Diabetes. (September 2014) - Jaser, Sarah S.; Patel, Niral; Rothman, Russell L.; Choi, Leena; Whittemore, Robin
Purpose: The purpose of the current study was to pilot-test a positive psychology intervention to improve adherence to diabetes management in adolescents with type 1 diabetes. Methods: A total of 39 adolescents (ages, 13-17 years) with type 1 diabetes and their caregivers were randomized to a positive psychology intervention (n = 20) or an attention control (education) intervention (n = 19). The intervention condition used positive psychology exercises (eg, gratitude, self-affirmation), small gifts, and parent affirmations to boost positive affect. Outcomes included frequency of blood glucose monitoring, quality of life, and glycemic control. Results: No main effects for treatment were observed at the 6-month follow-up. However, there was a significant association between adolescents' levels of positive affect and measures of adherence, including self-report and meter downloads of glucose monitoring. Conclusions: The results from the current study support the assertion that positive affect in the context of diabetes education is an important factor to consider in adolescents with type 1 diabetes.